Find the sum up to infinite terms
1 + 1 2 1 + 8 0 1 + 4 4 8 1 + 2 3 0 4 1 + …
Also see
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The series can be written as
n = 1 ∑ ∞ 2 2 n − 2 ⋅ ( 2 n − 1 ) 1 ⇒ 2 n = 1 ∑ ∞ 2 2 n − 1 ⋅ ( 2 n − 1 ) 1
The latter expression resembles that of the Maclaurin series representation of tanh − 1 ( x ) .
tanh − 1 ( x ) = n = 1 ∑ ∞ ( 2 n − 1 ) x 2 n − 1 tanh − 1 ( 2 x ) = n = 1 ∑ ∞ 2 2 n − 1 ⋅ ( 2 n − 1 ) x 2 n − 1
Hence, with x = 1
n = 1 ∑ ∞ 2 2 n − 2 ⋅ ( 2 n − 1 ) 1 = 2 tanh − 1 ( 0 . 5 ) ≈ 1 . 0 9 8 6
Note: By applying the properties of hyperbolic functions, it can be shown that tanh − 1 ( 0 . 5 ) = 2 ln 3
Problem Loading...
Note Loading...
Set Loading...
l n ( 1 − x 1 + x ) = 2 x + 3 2 x 3 + 5 2 x 5 + 7 2 x 7 . . . . . . . .
Replace x = 2 1
A n s w e r = l n 3